The Use of Kahoot Media in Arabic Language Learning to Improve Students' Ability to Understand Reading Texts - Wilda Nur Solihat; Agus Gunawan; Obby Syukri Mahdiyin; Rijaludin Iqbal Fauzi (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to determine the effectiveness of Kahoot media in Arabic language instruction in improving students' reading skills. It employed a quasi-experimental method with a pre-test and post-test design involving a single experimental group. The participants were seventh-grade students at SMP Al-Azhar Cairo Bandung. The primary focus of this study was to compare students' reading abilities before and after the implementation of the interactive media Kahoot and to evaluate whether it was more effective than traditional teaching methods. The results indicated that students' reading skills before using Kahoot were relatively low, with an average score of 50.8, which falls into the 50–59 category based on interpretation criteria. After the implementation of Kahoot, a significant improvement was observed, with the average score rising to 82.4, classified as